Speed and Scaling: An Investigation of Accelerated Firm Growth. (8th October 2022) - Belitski, Maksim; Stettler, Tatiana; Wales, William; Martin, Jeff
Abstract: While most firms do not grow, a small number of firms are able to maintain and accelerate their growth over time. Researchers, practitioners, and policymakers continue to question the factors which increase a firm's chances of growing rapidly and becoming a more powerful economic driver. Using a robust longitudinal data set from the United Kingdom (UK) during the period from 2000 to 2017, we investigate the propensity of firms to accelerate growth in sales, employment, market share, and productivity. We report varying effects of firm characteristics, industry competitive factors, and regional factors as drivers of accelerated growth. This study will help policymakers and firm managers understand the forces behind different types of acceleration, and it provides a foundation for future research on the speed of firm growth.